2007
DOI: 10.1210/er.2007-0022
|View full text |Cite
|
Sign up to set email alerts
|

Extranuclear Steroid Receptors: Nature and Actions

Abstract: Rapid effects of steroid hormones result from the actions of specific receptors localized most often to the plasma membrane. Fast-acting membrane-initiated steroid signaling (MISS) leads to the modification of existing proteins and cell behaviors. Rapid steroid-triggered signaling through calcium, amine release, and kinase activation also impacts the regulation of gene expression by steroids, sometimes requiring integration with nuclear steroid receptor function. In this and other ways, the integration of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
368
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(387 citation statements)
references
References 201 publications
9
368
0
10
Order By: Relevance
“…Although the underlying mechanism has not been investigated as yet, this observation is consistent with the existence of repeated cyclic interactions between ERα and cognate partners during target gene transactivation, a concept developed by several authors [31,42,43], is implicated in this dynamic LxxLL-coactivator recruitment is unknown. Investigating such a possibility seems to us of primary importance.…”
Section: Relationship Between Ligand-induced Recruitment Of Coactivatsupporting
confidence: 66%
“…Although the underlying mechanism has not been investigated as yet, this observation is consistent with the existence of repeated cyclic interactions between ERα and cognate partners during target gene transactivation, a concept developed by several authors [31,42,43], is implicated in this dynamic LxxLL-coactivator recruitment is unknown. Investigating such a possibility seems to us of primary importance.…”
Section: Relationship Between Ligand-induced Recruitment Of Coactivatsupporting
confidence: 66%
“…Studies support mitochondrial trafficking of an increasing number of nuclear receptors and transcription factors including ERα, ERβ, thyroid hormone receptor, glucocorticoid receptor, Nur 77, PPARgamma 2, RXR, RAR, AR, A-RAF, telomerase, Connexin 43, AP1, CREB, NF-k B, p53, c-Myc, HMGA1, TFAM, TFB1M, and TFB2M (Rodrigues-Sinovas et al, 2006;Yuryev et al, 2000;Santos et al, 2006;Hammes and Levin, 2007;Lee et al, 2007;. How they are targeted is not discerned, but most contain at least one F/LXXLL motif and/or are bound by Hsp90/70 in the cytosol.…”
Section: Mitochondrial Trafficking Of Erβmentioning
confidence: 99%
“…Our studies indicate ERβ, along with Tom20 and/or Hsp90 are localized to the mitochondria (Figure 2). Since studies purport that ER functions in the mitochondria, then ERβ should be targeted to either Tom20 or Tom70 receptors (Hammes and Levin, 2007). Receptor preference may depend on ligand induced conformational change in the receptor, and studies show that estrogen increases mitochondria localization of ERβ (Chen et al, 2004a).…”
Section: Mitochondrial Trafficking Of Erβmentioning
confidence: 99%
“…However, recently the FASEB steroid signaling work group suggested that "membrane-initiated steroid signaling" and "nuclear-initiated steroid signaling" are more appropriate terminologies (Hammes and Levin, 2007). The nuclear-effects on a variety of tissues that involves gene stimulation as well as gene repression (Herbison, 1998, Couse and Korach, 1999, Nilsson et al, 2001, Stossi et al, 2006, Kininis et al, 2007.…”
Section: Nuclear-initiated Signaling Of E2mentioning
confidence: 99%
“…It has become clear that there are "indirect" genomic actions of estrogen in the brain that do not require nuclear targeting of estrogen receptors and therefore are classified as "membraneinitiated" signaling of estrogen (for review (Kelly and Levin, 2001, Bryant et al, 2006, Hammes and Levin, 2007). Such signals that are initiated by E2 at the plasma membrane can trigger intracellular signaling events that result in gene transcription.…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%